Quality of care: Measuring a neglected driver of improved health - Yoko Akachi; Margaret E. Kruk (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The quality of care provided by health systems contributes towards efforts to reach sustainable development goal 3 on health and wellbeing. There is growing evidence that the impact of health interventions is undermined by poor quality of care in lower-income countries. Quality of care will also be crucial to the success of universal health coverage initiatives; citizens unhappy with the quality and scope of covered services are unlikely to support public financing of health care. Moreover, an ethical impetus exists to ensure that all people, including the poorest, obtain a minimum quality standard of care that is effective for improving health. However, the measurement of quality today in low- and middle-income countries is inadequate to the task. Health information systems provide incomplete and often unreliable data, and facility surveys collect too many indicators of uncertain utility, focus on a limited number of services and are quickly out of date. Existing measures poorly capture the process of care and the patient experience. Patient outcomes that are sensitive to healthcare practices, a mainstay of quality assessment in high-income countries, are rarely collected. We propose six policy recommendations to improve quality-of-care measurement and amplify its policy impact: (i) redouble efforts to improve and institutionalize civil registration and vital statistics systems; (ii) reform facility surveys and strengthen routine information systems; (iii) innovate new quality measures for low-resource contexts; (iv) get the patient perspective on quality; (v) invest in national quality data; and (vi) translate quality evidence for policy impact.
Keywords: 330; health interventions; health systems; quality of care; universal health coverage